Pengaruh Periklanan dan Kualitas Pelayanan Terhadap Minat Kunjung Ulang pada Waterpark Singapura Tulungagung - Jeri Okzy Nanda Putra; Bayu Cahyoadi (Indonesian Journal of Strategic Management, 2023)
This study aims to determine the effect of advertising (advertising) and service quality (service quality) on intention to return to the Singapore Waterpark. Applying the right marketing strategy will bring in tourists and make tourists who have already come have the desire to visit again. Interest in return visits is a person's encouragement to carry out activities to return to destinations that have been visited. In addition, interest in repeat visits is also supported by the quality of service. Service quality is an effort to meet the needs and expectations of tourists and provide accuracy in balancing tourist expectations. The type of research used is quantitative with this research design included in non-experimental research. The data collection method used a questionnaire to 98 respondents using cluster random sampling. The data analysis technique uses multiple linear regression tests to answer the research hypothesis. The results of the study show that: 1) Partially, there is an effect of advertising on the intention to revisit at Tulungagung Singapore Waterpark. 2) Partially, there is an influence of service quality on interest in repeat visits at Tulungagung Singapore Waterpark. 3) Simultaneously there is the influence of advertising and service quality on the intention to revisit the Tulungagung Singapore Waterpark. The result of the coefficient of determination is 0.349 or 34.9%. With a residual value of R Square 64.1% influenced by other variables not examined in this study.